Brokerage Intermediation and Digitization in Attracting Urban Middle-Class Professionals in NEPSE - Karki, Dipendra; Upadhyay, Akash; Giri, Sonika; Regmi, Yuba Raj (NCC Journal, 2025)
The study aims to analyze the importance of traditional brokerage firms and electronic trading platforms in promoting capital market participation among the urban middle class professionals in the context of Nepal. It examines how the accessibility of the platform, the transaction cost reduction, financial awareness, mediated through investor confidence, affects participation behaviour of a fast-growing group of retail investors on NEPSE. The research design was descriptive-analytical. The primary data were collected through a structured questionnaire from 360 urban middle-class professional investors actively trading in the Nepal Stock Exchange (NEPSE) through licensed brokerage firms or digital platforms. Five point Likert scale was used for a purposive sampling technique. The study employed descriptive statistics, Pearson correlation, multiple regression, mediation analysis (PROCESS macro), one-way ANOVA and Cronbach’s Alpha for instrument reliability, which were analysed in SPSS v.26. The results indicate that ease of platform use, responsiveness of the broker service, and transaction costs and financial awareness are the most important factors influencing market participation. The majority of respondents use digital platforms on a daily and weekly basis, with more than two thirds looking at self-directed digital trading and using broker advisory services as well. The regression results show that ease of access (β = 0.318), financial awareness (β = 0.284) and transaction cost reduction (β = 0.261) are significant factors to predict participation. Mediation analysis reveals that investor confidence partially mediates the relationship between digital platform attributes and capital market participation. ANOVA results show that investor confidence has significant differences among the professional groups. The sample is limited to Kathmandu Valley, limiting generalizability. The study offers empirical evidence on co-determinators of market participation in an emerging economy.